Sistem Penunjang Keputusan Penerima Kartu Indonesia Pintar Menggunakan Metode Simple Additive Weighting (SAW) - Andi Saryoko; Sholihin Muttaqin; Rahmat Hidayat (Universitas Bina Sarana Informatika, 2019)
Education is very important given the Government programs which require a minimum of 9 years of education, but many societies among medium size down unable to finance the education of their sons and daughters to 9 years. Indonesia Smart program is one of a national program that aims to increase the number of elementary and secondary education participation, increase sustainability education marked with menurunya numbers dropouts, as well as improving secondary education students readiness to enter the job market or proceed to higher education.In this research will be made a decision support system (SPK) to facilitate in the selection criteria for the Smart Card recipient Indonesia students who deserve help, the method used in this research is the Simple Additive Weighting (SAW), this method was chosen because it can determine the value weights for each attribute, and then do the perangkingan process will determine the alternatives to get more accurate results are eligible to receive smart cards help indonesia .By applying the method of Simple Additive Weighting (SAW) hope to provide ease in taking decisions which are appropriate and accurate.